Colour names in the structure of phraseological units in Spanish and Ukrainian - Чернецька, Н. В. (Studia Philologica, 2019)
Phraseological units which include colour names in Spanish language are investigated. The author analyses how color terms may influence on the total meaning of a phraseological unit. The article deals with the national cultural component “colour” in the phraseological units in Spanish language. The subject of the research determines the application of the comparative method. In this connection we use the linguistic facts of some national variants in Spanish language as well as in Ukrainian language. The results of the article confirm the forming of the national symbolism of colour in Spanish under the influence of the extralinguistic factors, transforming the colour into the national cultural component. The research materials and results can be applied in the sphere of such contiguous disciplines as intercultural communication, linguistics, translation theory and practice, studying Spanish by Ukrainian-speaking students, as well as in writing test books and other teaching material on lexicology. Research of colour names in Spanish language with its comparison with Ukrainian colour names shows that phraseological units with colour names are characterized with some similarity. Phraseological knowledge facilitates the reading of political essays as well as works of literature. The process of thinking in the educational progress cannot be overrated. In this learning the images are the material for solving the tasks. These images are phraseological units with colour names. They are the means of figurative images of ambient reality and simultaneously they enrich the intellect and spiritual inner awarenesses of an individual.